The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41571-022-00687-1
|View full text |Cite
|
Sign up to set email alerts
|

Systemic therapy for early-stage breast cancer: learning from the past to build the future

Abstract: The treatment of breast cancer has improved dramatically over the past century, from a strictly surgical approach to a coordinated one, including local and systemic therapies. Systemic therapies for early-stage disease were initially tested against observation or placebo only in adjuvant trials. Subsequent clinical trials focusing on treatment ‘fine-tuning’ had a marked increase in cohort size, duration and costs, leading to a growing interest in the neoadjuvant setting in the past decade. Neoadjuvant trial de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 113 publications
(126 reference statements)
0
30
0
Order By: Relevance
“…This study examined the predictive factors of NAC per se for pCR in breast cancer. In recent years, with the development of therapeutic agents and advances in breast cancer treatment strategies, more and more treatment options are being used in neoadjuvant therapy, such as neoadjuvant targeted therapy, neoadjuvant endocrine therapy, and neoadjuvant immunotherapy [ 60 ], and more studies are needed to explore the role of these options, alone and in combination, in neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This study examined the predictive factors of NAC per se for pCR in breast cancer. In recent years, with the development of therapeutic agents and advances in breast cancer treatment strategies, more and more treatment options are being used in neoadjuvant therapy, such as neoadjuvant targeted therapy, neoadjuvant endocrine therapy, and neoadjuvant immunotherapy [ 60 ], and more studies are needed to explore the role of these options, alone and in combination, in neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…BC is the most common malignancy in women, and one of the three most common cancers worldwide. Although therapy has progressed over the past years and early diagnosed BC is now considered potentially curable, there is still a need for newer targeted therapies which make the prospect of long-term disease control in metastatic BC an increasing reality [ 29 ]. Recently, it has been reported that redox-sensitive molecules such as Nrf2 may play a role in the control of BC progression [ 30 ] and the development of drug resistance and metastasis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As we demonstrated in the four-quadrants analysis of NAC response and survival outcomes, integration of both short-term and long-term clinical outcomes is more meaningful in guiding clinical decisions. Residual cancer burden (RCB), which is a continuous index to measure treatment responses based on primary tumor and nodal metastases, is considered the better endpoint to replace pCR for the neoadjuvant treatment responses in clinical trials [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%